PERAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI MTS AL HIKMAH CUPEL, JEMBRANA, BALI - Samsul Hadi (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2016)
credibility principal's leadership in implementing management preformance improve the quality of education, especially teachers to improve and menghasilkan best learners. In detail the focus of this study are described in the form pertayaan as follows; Efforts are made by the headmaster in improving the quality of education in MTs Al Hikmah Cupel? What factors that support and hinder the headmaster leadership in improving the quality of education in MTs Al Hikmah Cupel? How headmaster steps taken in improving the support and overcome obstacles in improving the quality of education in MTs Al Hikmah Cupel?. This research is descriptive, namely in the form of descriptions of words or sentences written or oral from the principal, subject teachers, homeroom and observable behavior. There is also in the form of figures but merely a supporter. researchers used a technique through participant observation, in-depth interviews and documentation. The factors supporting and inhibiting strategies principals in the development and improvement of the quality of teachers in Islamic Elementary School 1 Airkuning Jembrana Bali is as follows: (a) factors that support: Teachers attend seminars / kursus.penataran / lecture again, etc., so that the quality of teachers increased the lead to quality of students also meningkat.yang result also improved the quality of students, teachers have also understood that he was a disciple so trying to learn again increase knowledge at every opportunity; (b) factors that hamper: Affairs of prosperity that is less noticed by the school often make teachers reluctant to work hard so that disrupt the learning process, less energetically because of depleted illness or family problems, state of students capable less well in lessons, learning ability of students are less because lazy. Keywords: The Role, The School Principal, MTs Al-Hikmah